THE EFFECTIVENESS OF PEER FEEDBACK TECHNIQUE THROUGH COOPERATIVE LEARNING TO IMPROVE STUDENTS' ABILITY IN WRITING NARRATIVE TEXTS : A Quasi-Experimental Research of Tenth Grade in Senior High School - Nuraeni (2014)
Penelitianinimengkajikeberhasilanpenggunaanteknikpeer feebackmelaluipembelajarankooperatifdalammeningkatkankemampuansiswadalammenulisteksnaratif. Enampuluhsiswakelassepuluh di kota Bandung berpartisipasidalampenenlitianini. Merekadikelompokankedalamduagrup; grupeksperimendangrupkontrol.Penelitianinimenggunakanmetode quasi eksperimen.Hasiltulisansiswadalamsesi pre-test dan post-test merupakanperolehan data yang dijadikanacuanuntukmenariksimpulan.Sebelumnya, tulisanmerekatelahdianalisismenggunakan rubric menulisdari Virginia Education 2012 denganmenilaipadaempataspekmenulis: organisasiteks, perbendaharaan kata, grammar, danmekanismepenulisan. Hasildaripenelitianinimenunjukanbahwapenggunaanteknikpeer feedbackantarsiswamampumeningkatkankemampuanmerekadalammenulisteksnaratif. Siswamerasasebayadannyamanuntukmemberikankomentarterhadaptulisantemannya. Dari itu, siswadapatmenikmati proses writing danberupayauntukmemperolehrevisitulisan yang lebihbaik. This study examines the effectiveness of using peer feedback technique through cooperative learning in improving students' writing ability of narrative text. Sixty tenth-grade students in Bandung participated in this study. The participants were divided into two groups; experimental and control groups. This study employed quasi-experimental design as the methodology. The data were obtained from students' writing product on pre-test and post-test. Students' writing were analyzed by using writing rubric from Virginia Education 2012. The writing aspects were focused on four: organization, vocabulary, grammar, and mechanics. The finding showed that peer feedback between students improved students' writing of narrative text. Students felt equal and comfort to share their ideas and comments on their friends' work during peer feedback activity. Since of that, students could appreciate the writing process and tried to acquire the better revision.